Study of Ultrasonic Wave Velocity in Organic Binary Mixture Liquids of Methyl Propyl Ketone and Bezaldehyde (MPK+C6H5CHO) at 308.15K (Bulletin of Pure and Applied Sciences – Physics, 2020)
The measurement and investigation of the ultrasonic velocity (U), density ( ),  viscosity ( ), adiabatic compressibility (  a ), intermolecular free length (Lf), Gibb’s  free energy (G), molecular volume (Vm), available volume (Va), free volume (Vf) and  specific acoustic impedance (Z) studied in binary liquid mixtures of Methyl Propyl  Ketone and Bezaldehyde (MPK+C6H5CHO) at 308.15K.